AKSES, FUNGSI, DAN POLA PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) OLEH PETANI PADA KAWASAN PERTANIAN KOMERSIAL DI KABUPATEN BANTUL - Christian, Ade Intan; Subejo, Subejo (University of Jember, 2018)
Information and Communication Technologies (ICTs) has been considered play an important role for supporting the need of new information and innovation for farmers. Extension and communication based ICTs in developing countries can be used for wider scope of activities including information related to various farming operations. This research discusses a new trend of emergence of ICTs in Bantul Regency for supporting daily life activities of farmer including agricultural activities. Research method of study was descriptive method. In general, farmers have been using television and radio with function for getting information, entertaining, and education. However, hand phone and smart phone to some extent have emerged as additional and important alternative media for farmer. The use of internet via smartphone has newly started to be utilized among farmer in Bantul Regency. Information on agriculture which accessed by farmers was still dominated by production aspect and marketing.